2022
DOI: 10.3390/pharmaceutics14061153
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Nephrotoxicity and Permeation of Vancomycin Hydrochloride Loaded Liposomes

Abstract: Drugs can be toxic to the fetus depending on the amount that permeates across the maternal–fetal barrier. One way to limit the amount which penetrates this barrier is to increase the molecular size of the drug. In this study, we have achieved this by encapsulating our model antibiotic (vancomycin hydrochloride, a known nephrotoxic agent) in liposomes. PEGylated and non-PEGylated liposomes encapsulating vancomycin hydrochloride were prepared using two different methods: thin-film hydration followed by the freez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…In addition, the results demonstrated that 89–93 and 100% of the standard DOX and CB were released from their relevant solutions after 2 and 2.5 h, respectively ( Figure 2 ), indicating the high efficacy of PEG-Lip-DOX, PEG-Lip-CB, PEG-Lip-DOX/CB, Lip-DOX, Lip-CB, and Lip-DOX/CB to control the drug release. Papp et al [ 42 ] also demonstrated that reversed-phase-synthesized PEGylated liposomes, compared to reversed-phase-synthesized non-PEGylated liposomes, caused a lower amount of drug release after 48 h (~20 vs. ~50%).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the results demonstrated that 89–93 and 100% of the standard DOX and CB were released from their relevant solutions after 2 and 2.5 h, respectively ( Figure 2 ), indicating the high efficacy of PEG-Lip-DOX, PEG-Lip-CB, PEG-Lip-DOX/CB, Lip-DOX, Lip-CB, and Lip-DOX/CB to control the drug release. Papp et al [ 42 ] also demonstrated that reversed-phase-synthesized PEGylated liposomes, compared to reversed-phase-synthesized non-PEGylated liposomes, caused a lower amount of drug release after 48 h (~20 vs. ~50%).…”
Section: Resultsmentioning
confidence: 99%
“…For the use of nanoparticles, premature drug release is a challenge that might be overcome by PEGylation [ 31 ]. In addition, Papp et al showed that PEGylated liposomes synthesized by the reverse phase method resulted in less drug release after 48 h than non-PEGylated liposomes synthesized by the reverse phase method [ 32 ].…”
Section: Physicochemical Identification Tests Of Lipo-let-pegmentioning
confidence: 99%
“…In an effort to reduce vancomycin-induced nephrotoxicity, we have successfully encapsulated vancomycin in polyethylene glycol-coated liposomes (PEG-VANCO-lipo) [ 14 ]. The particle size of PEG-VANCO-lipo was found to be less than 200 nm, and they were characterized for stability, zeta-potential change, and in vitro release kinetics, as reported in our earlier publication [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to reduce vancomycin-induced nephrotoxicity, we have successfully encapsulated vancomycin in polyethylene glycol-coated liposomes (PEG-VANCO-lipo) [ 14 ]. The particle size of PEG-VANCO-lipo was found to be less than 200 nm, and they were characterized for stability, zeta-potential change, and in vitro release kinetics, as reported in our earlier publication [ 14 ]. We have previously carried out in vitro cytotoxicity studies on kidney cells (rat kidney epithelial cells, NRK-52E) using PEG-VANCO-lipo and found it to be minimally toxic compared to vancomycin alone [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation